2014
DOI: 10.1371/journal.pone.0085309
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Assessment in Patients with Axial Spondyloarthritis Compared to Healthy Controls: A Technology-Based Approach

Abstract: IntroductionTraditionally, assessment in axial Spondyloarthritis (aSpA) includes the evaluation of the capacity to execute tasks, conceptualized as physical function. The role of physical activity, defined as movement-related energy expenditure, is largely unknown and almost exclusively studied using patient-reported outcome measures. The aims of this observational cross-sectional study are to compare physical activity between patients with aSpA and healthy controls (HC) and to evaluate the contribution of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 39 publications
(60 reference statements)
5
100
0
3
Order By: Relevance
“…Sedentary behaviour in AS is under-researched and poorly understood. Few studies have objectively measured sedentary behaviour and PA in an SpA cohort [18,19]. Methodological limitations and heterogeneity of accelerometry outcome variables limit direct comparisons to these studies and prevent firm conclusions from being drawn [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sedentary behaviour in AS is under-researched and poorly understood. Few studies have objectively measured sedentary behaviour and PA in an SpA cohort [18,19]. Methodological limitations and heterogeneity of accelerometry outcome variables limit direct comparisons to these studies and prevent firm conclusions from being drawn [17].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review identified two studies which objectively measured PA in adults with AS and compared results to population controls [17][18][19]. Results from these studies are equivocal; PA levels among adults with AS may be lower than, or equivalent to, the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Semiautomated accelerometer algorithms with proven psychometric properties exist in patients with parkinsonism and stroke, but are limited to selected tests such as walking, standing, and sit-to-stand (STS) activities 23,24,25 . In patients with axSpA, the use of body-worn sensors is still in its infancy and focuses on accelerometer algorithms for physical activity assessment 26 . Therefore, our proof-of-concept study aimed to (1) present the development of the instrumented BASFI (iBASFI), adding fully automated algorithms during PBM to obtain activity capacity outcomes in axSpA, (2) evaluate the test-retest reliability of the automated algorithms and their criterion validity in comparison with manual feature selection in axSpA, (3) compare these novel activity capacity outcomes for construct validity to chronometer-based PBM and the BASFI; and (4) create a preliminary optimal set of PBM that reflected the BASFI best.…”
Section: Rheumatologymentioning
confidence: 99%
“…Des études cas-témoin montrent certes que la consommation maximale en oxygène à l'effort exprimée en moyenne est diminuée chez les patients atteints de spondyloarthrite comparativement aux témoins indemnes [5,6]. La diminution de l'activité physique attendue en conséquence chez ces patients n'est en revanche qu'inconstamment retrouvée [7][8][9][10]. Dans l'étude la plus vaste, regroupant plus de 2000 patients sué-dois, les deux tiers avaient une activité physique en accord avec les recommandations de l'Organisation mondiale pour la santé, et le risque standardisé d'activité physique était de 1,09 (IC95 1,04-1,15), indiquant un niveau d'activité physique légèrement supérieur à celui observé dans la population générale [8].…”
Section: Prérequisunclassified